A novel technique for generating desired vibrations in structure. Issue 176 (21st November 2016) - Sarabi, Behrouz Kheiri; Sharma, Manu; Kaur, Damanjeet; Kumar, Navin
ABSTRACT: A novel technique is presented for exciting desired transient vibrations in a structure. A cantilevered plate instrumented with piezoelectric sensor and actuator is used as a test-structure. Finite element model of the test-plate is developed using Hamilton's principle. Finite element model is reduced to first two modes using orthonormal modal truncation and then this reduced model is converted into a state-space model. Tracking optimal control is then employed to obtain desired transient curves simultaneously, of first two modes of vibration. Theoretical findings are verified by conducting experiments, for experimentation, Kalman observer is used to estimate first two modes and Labview software is used for interfacing. Presented strategy can be used to do dynamic vibration testing of a product by forcing the product to experience same transient vibrations that it is expected to experience in field.